NILAI-NILAI SUFISME DALAM KUMPULAN PUISI HADRAH KIAI KARYA RAEDU BASHA - Asy’ari, Hasyim (Jurnal Sastra Aksara, 2019)
Literature is complex and deep humanity. there is more literary genre of poetry, whose emphasis on interpretation requires an intense reading and research, so out of it comes the term of reality about anything as well as the knowledge of God in society. Call it the value of Sufism in poetry. In the values of Sufism, there were four things found in the collection of poetry in the poetry book of Hadrah Kiai by Raedu Basha, among them were Shari'a, tarekat, essence, and makrifat. The existence of the fourth symbol of that Sufism level was very important to be examined. The research method used in this research was qualitative descriptive research. Descriptive qualitative was an approach in researching an object, a system of thought, or even a class of event in the present, and the obtained data was not in the form of numbers, but in the form of words or sentences obtained from the text. In the results of this research, the poetry book of Hadrah Kiai by Raedu Basha discussed four things, they were Shari'a, tarikat, essence, and makrifat. While the obtained data from the poetry book of Hadrah Kiai by Raedu Bashadari the fourth research problem were 32 data with details as follows. 11 research problem data about syariat, 9 research problem data about tarekat, 6 research problem data about reality, and 6 research problem data about makrifat. The four problems described physical cleanliness that also wanted spiritual cleanliness in different ways.